Insuficiencia jurídica en la ley del anciano sobre las actividades ocupacionales preferentemente vocacionales y remuneradas que debe percibir el anciano - Monteros Montero, Andrea Katherine (2016)
The Constitution of the Republic of Ecuador establishes the régime of the good one the same one that institutes to live and it recognizes the social justness and it applies universality principles, equality, progressivity, solidarity and not discrimination principles guided to generate an integral protection of all its inhabitants throughout its lives understood from the human being's birth until the last minute of its life and with constitutional special and high-priority attention according to the normative one to people of third age or bigger adults. Ecuador in the last 15 years has suffered an economic crisis with fateful results the lack of work sources it has provoked that the active population economically emigrates to other countries of Europe looking for better days for her families while the economically active population that is in our country unemployed is or underemployed. As consequence of this migration we can see that in some cities he/she meets a significant number of population old unemployed with few possibilities or none of getting a work. To speak at the present time of bigger adult is worrying it seems that the society doesn't take conscience in that we all will end up being old in some moment The aging process is a problem that embraces the whole society for the enormous repercussions that these he/she has in the life of all the people and it is for that reason it should be had the attention and the permanent study. If we put attention the old an end he/she has left loading of a negative value inside our society when the oldest male in the clan was advice source and all decision went by its analysis loaded with experience. This collective blindness has determined the youth's primacy and the novel thing above all without any opportunity of getting a work for the old ones, our old men are subject of all type of taunts and asilamiento the law that seeks protection them it has transformed into dead letter. Art. 54 of the Political Constitution of the State say: "The State will guarantee to people of the third age and the pensioners, the right to special attendance that assures them a worthy level of life, integral attention of gratuitous health and preferable tributary treatment and in services." CONSTITUTION OF THE REPUBLIC OF THE EQUATOR, Corporation of Studies and Publications, 2004. In the case of their labor rights it is well-known that the biggest adults don't either have access possibilities to work sources for the fact that the society considers that he/she no longer has anything to contribute to the productive apparatus, you cannot exploit its productive force in comparison with a young person or to consider that when having worked for many years it is no longer necessary that they follow it making that is to say many prejudices taken root in the imaginary one exist collective regarding this vulnerable group of the society that makes these people full with experiences to continue contributing to the activity from their own capacities and abilities. Our Code of little Work or almost anything contemplates on the work for people of the third age and the pensioners being infringed this way the juridical constant precept in Art. 54 of the Constitution. It is very common to see people that without belonging to the third age, for labor dispositions they have gone into retirement and they have not been able to reinstate to the group of active workers, even many of them for not saying all are responsible for a home, that is to say, it handcuffs or children that to maintain and to educate, in short, you load family, the same ones that have been flings to their luck because the family head for their age or pensioner's condition has prevented him/her to be able to be hired in some company, factory or any work type again, making him/her feel as an useless being, other people's clerk. The remunerations that the pensioners and people of the third age receive, for the changes that have taken place in the salary and economic aspect in the country, have produced that with the change of currency of sucres to dollars are little less than insignificant that don't cover the most minimum in the basic necessities of any person. According to Retired Cabanellas he/she is "the person that perceives jubilation or passive haberes for their last services. Quantity or amount of what is perceived without benefit of current effort, and for the deployed activity until to reach certain age or to be in another situation, as the disability that you/they advance such a right or compensation." As Cabanellas it defines it, a pensioner is not but a person that is entitled to a benefit around borrowed services for a company or employer, without it means it uselessness by no means, as mistakenly he takes it the society. Juridical elementary dictionary Guillermo Cabanellas of towers edition 2003. The old man's Law in Art. 4 settle down it corresponds to the Ministry of Social Well-being the protection to the old man, for that which, it will foment the following actions: to) to Make campaigns of promotion of attention to the old man, in all and each one of the counties of the country; b) to Coordinate with the Secretary of Social Communication, Provincial Council, Municipal Town councils, in the diverse programs of attention to the old man; c) to Grant consultantship and permanent qualification to retired people or in jubilation process; d) to Impel programs that allow the old men to develop occupational, preferably vocational and remunerated activities stimulating to the institutions of the private sector so that they make same work; and, Law of the Old man and) to Stimulate the formation of voluntariado groupings guided to the old man's protection and to supervise their operation. At the present time the public institutions and deprived then they don't fulfill that settled down in the Old man's Law in Art. 4 literal d) with respect to the occupational and preferably vocational remunerated activities, because this institutions inside the work plan yearly have not included to carry out these works in an obligatory way that you/they help the biggest adults to have this type of activities remunerated by the works that have carried out with effort valuing the work that these they can develop. A solution to the problem of the unemployment of people of the third age or pensioners, would be giving them a new opportunity to work, in works that don't require physical neither mental bigger effort, since with it would be achieved it to improve its self-esteem, because they will stop this way to feel useless beings, desmotivados and inactive, because we know all that the work dignifies the person and inclusive improvement its mental state and of health, considering that this important group of people bill with capacity and experience in many fields of the manual work mainly since with it would be achieved it to improve its self-esteem.